Sexualidade e tabus sexuais: desejo, formação e cicatrizes - Nascimento, Mauro Antônio do (Universidade Federal de São Carlos, 2024)
This research sought to understand a priori sexual desire and a posteriori taboos. In this trajectory, the concept of enlarged sexuality was evidenced, which, according to Laplanche (2018), was the main discovery of psychoanalysis. By bringing this concept closer to the "Eros of the divine Plato", Freud revealed the different destinies of the drives. The evidence, found throughout this research work, was then analyzed in the light of the conceptions of the Critical Theory of Society. It was identified, in this way, that Eros is a formative principle, however, it was verified, in the unfolding of this analytical work, that sexual taboos have become principles of deformation of individuals. Therefore, for a better understanding of taboos, we chose to conceptualize the fundamental taboos as primary and the sexual taboos as secondary. This distinction is crucial, because the fundamental taboos have become civilizing principles and the repression that comes from the primary taboos is necessary, as Freud considered, for civilizational existence. However, by expanding sexual restrictions, sexual taboos triggered a process of regression to barbarism. In fact, the acts of extreme violence have transformed human daily life into a scene of horror. Based on Freudian theory, we sought to understand the genesis of violence. Thus, by analyzing Eros and its antithetical forces, a consistent theory for understanding the human condition was found. Thus, when referring to the analysis of the concept of false projection or "pathic projection", carried out by Theodor Adorno and Max Horkheimer, the psychic mechanisms of disqualification of the other in their human condition were evidenced and, therefore, it was possible to identify the resources mobilized by fascists to annihilate differences.
Sexuality and sexual taboos: desire, formation and scars
Keywords: Psicanálise; Eros; Sexualidade ampliada; Tabus fundamentais; Tabus sexuais; Psychoanalysis; Eros; Enlarged sexuality; Fundamental taboos; Sexual taboos; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL